2015
DOI: 10.3329/seajph.v4i2.23691
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing fertility preference of a developing country during demographic transition: Evidence from Bangladesh

Abstract: Fertility preferences indicate the extent of intended control over reproductive outcomes, and are therefore vital components in the analysis of individual fertility behavior and aggregate fertility trends of a country. Despite extensive research, dissimilarities remain regarding the prior stated fertility preferences and subsequent fertility behavior, especially in case of developing countries like Bangladesh; where third stage of demographic transition begun as a result of continuous assessment. The purpose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
0
12
1
Order By: Relevance
“…There was no significant effect of wealth index on women's fertility. 19 This finding is not compatible with those of prior studies. 15,18 Women who dwell in rich families have approximately twice as few children as those living in proletarian households.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…There was no significant effect of wealth index on women's fertility. 19 This finding is not compatible with those of prior studies. 15,18 Women who dwell in rich families have approximately twice as few children as those living in proletarian households.…”
Section: Discussioncontrasting
confidence: 87%
“…Women dwelling in the western region had comparatively lower fertility rates than those dwelling in the central region. The study performed in Bangladesh 19 reported that fruitfulness is not identical in every region of Bangladesh. Non-Muslim women had a lower fertility rate in Bangladesh than Muslim women.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…For instance, Duvendack and colleagues (2016) showed the association of women empowerment and the trend of fertility among women by years' span [5]. AMF Rabbi (2014) sorted out the fertility preference and concluded that the expected time interval for the next children plays a crucial role in the TFR scenario in Bangladesh [12]. Some other studies generally focused on the relationships of women's decision making autonomy with either the use of contraception or maternal health care services [6,7,10,[13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the available literature, it is evident that assessing the determinants of fertility intension and exploring the extent to which they are associated with having more than desired children are crucial for the performance of family planning programs initiatives and for the population policy of a country [12]. Many studies around the world have conceptualized different pathways that affect fertility preference and identified socio-economic and demographic factors of fertility preferences and actual demand for children.…”
Section: Introductionmentioning
confidence: 99%